Performance of Lower Ventilation Opening to Improve Air Change per Hour in Classroom at Tropical Humid Region (Case Study: Palembang City) - Tri Woro Setiati,; Sandra Eka Febrina,; Fajar Sadik Islamia, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Fresh air circulation in a room had an impact on indoor air quality. In today’s pandemic, good fresh air circulation is one of the main strategies to prevent viruses from spreading through air molecules. A good ventilation opening design influences indoor air exchange. This research conducts a test on lower ventilation opening design that can maximize natural ventilation performance in a classroom. This test aimed at a recommendation for schools in the tropical humid region so they can hold offline learning with low virus spreads. Natural ventilation optimization should be a solution because not everyone can afford mechanical air filters or virus killers. This research used an experimental method. Computer simulation test variables were classroom openings consisting of existing openings, new outlets/openings, and lower ventilation opening. Parameters of observation are wind velocity, air circulation pattern, and air change per hour. This evaluation compares the experiment result to Air Change per Hour (ACH) threshold limit provision required in Indonesia. The result of the experiment shows outlet/opening addition provides a better impact on ACH escalation than with only existing classroom opening. And when the existing opening is closed, lower ventilation opening had good performance in achieving the ACH threshold limit provision requirements which were 9,8 ACH.